Diagnostic accuracy of stereotactic brain biopsy for intracranial neoplasia in dogs: Comparison of biopsy, surgical resection, and necropsy specimens. (16th April 2019) - Kani, Yukitaka; Cecere, Thomas E.; Lahmers, Kevin; LeRoith, Tanya; Zimmerman, Kurt L.; Isom, Scott; Hsu, Fang‐Chi; Debinksi, Waldemar; Robertson, John L.; Rossmeisl, John H.
Abstract: Background: Stereotactic brain biopsy (SBB) is a technique that allows for definitive diagnosis of brain lesions. Little information is available regarding the diagnostic utility of SBB in dogs with intracranial diseases. Objective: To investigate the diagnostic accuracy (DA) of SBB in dogs with brain tumors. Animals: Thirty‐one client‐owned dogs that underwent SBB followed by surgical resection or necropsy examinations. Methods: Retrospective observational study. Two pathologists blinded to SBB and reference standard diagnoses reviewed histologic specimens and typed and graded tumors according to World Health Organization and revised canine glioma classification criteria. Agreement between tumor type and grade from SBB were compared to reference standards and assessed using kappa statistics. Patient and technical factors associated with agreement also were examined. Results: Stereotactic brain biopsy specimens were obtained from 24 dogs with gliomas and 7 with meningiomas. Tumor type agreement between SBB and the reference standard was observed in 30/31 cases (κ = 0.95). Diagnostic concordance was perfect for meningiomas. Grade agreement among gliomas was observed in 18/23 cases (κ = 0.47). Stereotactic brain biopsy underrepresented the reference standard glioma grade in cases with disagreement. The DA of SBB was 81%, with agreement noted in 56/69 biopsy samples. Smaller tumors and fewer SBB specimens obtained were significantly associated with diagnostic discordance. Conclusions and Clinical Importance: The DA of SBB readily allows for the diagnosis of common brain tumors in dogs. Although glioma grade discordance was frequent, diagnoses obtained from SBB are sufficient to currently inform therapeutic decisions. Multiple SBB specimens should be collected to maximize DA.